To Evaluate the Management of Epididymo-Orchitis at Tertiary Care Hospital - Altaf Hussain Ghumro, Inayat Ali Zardari, Sadia Ayoub, Mashooq Ali Khowaja, Aijaz Hussain Memon, Zulfiqar Ali Imtiaz Memon, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Epididymo-orchitis is common condition in scrotum found in surgical practice. It is commonly seen in young males. It can occur at any age. The common age is between 2nd to 4th decades of life. Its duration of illness is 6 weeks in acute condition and 12 weeks in in chronic conditions. It mostly occurs associated with sexually transmitted diseases. Chlamydia trachomatis and Neisseria gonorrhea are the common causative organisms. After age 40, the common organisms causing this disease are Escherichia Coli and Coliform bacteria found on G.I.T. There are also other causes of this disease. It is mostly managed conservatively but it can be operated it the condition develops complications. Even Orchidectomy is also done in some conditions. Objective: To evaluate the management options in epididymo-orchitis . Material methods: This is a cross sectional study done at surgical Unit 1 of Peoples Medical Hospital (PMCH) Nawabshah. The duration of study was one year from 10th August 2019 to 9th July 2020. All the patients were admitted through Surgical out Patient Department (SOPD) and emergency department of Peoples Medical College Hospital (PMCH) Nawabshah. Approval of study was taken from Ethical committee. Detailed history and thorough clinical examination was done. Routine investigations were done apart from viral markers including HIV. Urine DR and Culture ,Ultrasound of Scrotum and CT Scan were done. Management was planned accordingly. Results: Total 65 patients were included in this study. Of them, 20 (31%) had left sided pathology, 40 (61%) had right sided and 5(8%) had bilateral. Testicular abscess formation was seen in 8 (12.3%) patients. In 2 (3.07%) patients, testicular infarction was noted. 1 (1.5%) patient became infertile due to bilateral involvement. 3 (4.6%) patients had developed psychosis. Conclusion: It is concluded that most of the patients were treated conservatively and in a few patients, incision drainage and orchidectomy was performed. Keywords: Epididymo-orchitis. Neiserria Gononrhea, E.Coli, Incision Drainage, Orchidectomy.